The Identification of Scientific Findings of Strategic Public Policies on the Prohibition of Using Plastic Bags in Stores, Markets and Supermarkets: A lesson for Biak Numfor Regency - Asmadianto Asmadianto; Karina Arfany Arfah (Department of Public Administration, Muhammadiyah University of Makassar, 2021)
This qualitative study aims to understand the identification of scientific evidence and the effect of local government policies on the prohibition of using plastic bags in shopping centers in Biak Numfor Regency. As a government, it can make regional policies to continue the sustainable development of all sectors, including developing a healthy environment free of plastic waste. To understand this effect, we have collected data from various literature and scientific studies of publications that also voice the importance of local government policies to keep the environment healthy from plastic waste. After we found the data, we analyzed it with a descriptive approach through coding, in-depth interpretation, and concluding. For our study to answer this study's questions, we pay attention to data validity and reliability principles. We follow the suggested data design. Our study found that the policy to prohibit plastic bags has resulted in maintaining the cleanliness of the residential environment where people live. However, on the other hand, there are still parties who are still disadvantaged by this policy. Thus, this result will be the initial stage of government efforts to preserve a healthy Biak Numfor Regency environment